Students' Environmental Knowledge Learning in the Era of Industrial Society 4.0 Reviewed from Digital Literacy Capability - Rahmatulloh; Napis (Universitas Pendidikan Ganesha, 2024)
The challenge of learning environmental knowledge in the era of industrial society 4.0 amidst the implementation of hybrid learning is low digital literacy capability. The implementation of hybrid learning requires students to have digital literacy capability, where students must be able to understand the real context presented in digital form. This research aims to analyze the effect of digital literacy on environmental knowledge. The research uses a quantitative approach, survey method, with regression analysis techniques. A sample of 50 students taking environmental knowledge courses were selected randomly. The data collection technique uses test instruments to measure environmental knowledge, while non-test instruments are used to measure digital literacy capability. The research results show that digital literacy has a positive influence on environmental knowledge. The higher a student's digital literacy, the higher their environmental knowledge. The findings state that digital literacy capability contribute 40% to environmental knowledge. Environmental knowledge learning can be improved by strengthening students' digital literacy so they can follow the flow of implementing hybrid learning. The results of this research have implications for strengthening students' digital literacy capability, and digitizing environmental knowledge learning.